2022
DOI: 10.15177/seefor.22-05
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Fuel Properties of Bambusa vulgaris of Different Age Groups and Their Effect on Producing Biofuel

Abstract: Bamboo can be used to produce solid, gaseous, and liquid fuels, as well as to generate heat and biofuels for transport and electricity. The main objective of this study was to investigate the physical and fuel properties of Bambusa vulgaris in three ecological zones for their utilization potential for the production of biofuels. Thirty-six samples of Bambusa vulgaris culms from 3 ecological zones in Ghana were milled to powder to assess the physical and fuel properties. The physical properties; moisture conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
1
0
1
Order By: Relevance
“…In addition to this, the internode diameter in the L. Victoria crescent (2.55 cm ± 1.22) was found to be significantly higher than in West Nile (measuring 2.29 cm ± 0.94) and Southern Highlands (measuring 2.31 cm ± 0.96). However, the internode diameter reported in this study was lower compared to the range of 3-9 cm reported by Antwi et al (2022), Wahab et al (2009) andGomes Neto et al (2021). This could be due to the underdevelopment of culms from a clump of three years old.…”
Section: Internode Length and Internode Diametercontrasting
confidence: 88%
See 1 more Smart Citation
“…In addition to this, the internode diameter in the L. Victoria crescent (2.55 cm ± 1.22) was found to be significantly higher than in West Nile (measuring 2.29 cm ± 0.94) and Southern Highlands (measuring 2.31 cm ± 0.96). However, the internode diameter reported in this study was lower compared to the range of 3-9 cm reported by Antwi et al (2022), Wahab et al (2009) andGomes Neto et al (2021). This could be due to the underdevelopment of culms from a clump of three years old.…”
Section: Internode Length and Internode Diametercontrasting
confidence: 88%
“…Sidack post-hoc test results revealed that the culm internode length in the L. Victoria crescent (25.27cm ± 5.05) was significantly higher than in the West Nile (24.02 cm ± 4.17) and Southern Highlands (23.15 cm ± 4.54). The average internode length for culms from fully grown clumps is reported to be 25-45 cm (Antwi et al, 2022;Darwis & Iswanto, 2018;Gomes Neto et al, 2021). This study shows that when a clump is about three years old, the new culms that grow (referred to as juveniles) have an average internode length similar to the average length of B. vulgaris reported by Wahab et al (2009).…”
Section: Internode Length and Internode Diametersupporting
confidence: 62%